TANTANGAN DALAM PENCIPTAAN SENI RUPA TRADISI DI ERA REVOLUSI INDUSTRI 4.0 - Karsam . (Jurnal Budaya Nusantara, 2019)
The industrial revolution 4.0 was an era where all aspects were made, carried out, carried out with tools and facilities that were all modern including the creation of traditional art. The order of human behavior in work that cannot keep up with changes in the digital age will be marginalized. This condition can marginalize and even destroy the existence of traditional art.This research was carried out by using qualitative method in which data are obained from observation, literature review and direct practice in the field, where the author is the actor of the creation of traditional art.The purpose of this study is to preserve and preserve the existence of traditional fine art on this earth, so the creators (Artists, Masters, Kriyawan, Craftsmen, etc.) must be able to use media, tools, materials, facilities that develop in this time. The author hopes that this research can benefit readers, researchers, reviewers and traditional art actors to continue working in this era of industrial revolution 4.0 without abandoning traditional artistic values.